father`s age is 3 times the sum of ages of his 2 children .after 5 yrs his age will be twice the sum of ages of the two children . find the present age of father

Let the children's ages be \( x \) and \( y \) and the father's age \( z \). So \( z=3(x+y) \) and \( z+5=2(x+y+10)\).
Then we get \( z=2x+2y+15 \).Then we can substitute \( z=3(x+y) \) which is \( z=3x+3y \).So \( x+y=15\),and \( z=45 \)

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestLet the children's ages be \( x \) and \( y \) and the father's age \( z \). So \( z=3(x+y) \) and \( z+5=2(x+y+10)\). Then we get \( z=2x+2y+15 \).Then we can substitute \( z=3(x+y) \) which is \( z=3x+3y \).So \( x+y=15\),and \( z=45 \)

Log in to reply

Let \(c\) be the sum of the 2 children's age and \(f\) be the father's age

\(f=3c\) ...(1)

\(5+f=2(c+10)\) ...(2)

Simplifying (2): \(5+f=2c+20\Rightarrow f=2c+15\)

Combining (1) and (2): \(3c=2c+15\). Therefore, we could get \(c=15\)

From (1): \(f=3c\), we could get the father's age: \(f=3(15)\Rightarrow f=45\)

Therefore, the father's present age is 45 years old.

Log in to reply